Adapting the Bogenhausen Dysarthria Scales (BoDyS) to Chilean Spanish Speakers: Face and Content Validation - Marcela Sanhueza-Garrido; Virginia García-Flores; Sebastián Contreras-Cubillos; Jaime Crisosto-Alarcón (Brain Sciences)
Background: Dysarthria is a neuromotor speech disorder that significantly impacts patients’ quality of life. In Chile, there is a lack of culturally validated instruments for assessing dysarthria. This study aimed to cross-culturally adapt the Bogenhausen Dysarthria Scales (BoDyS) into Chilean Spanish and to conduct face and content validation. Methods: The adaptation process included translation and back-translation, followed by validation by a panel of experts. Clarity, format, and length were evaluated, and the Kappa index (KI), content validity index (CVI), and content validity ratio (CVR) were calculated to confirm item relevance. A pilot test was subsequently conducted with ten speech–language pathologists to apply the adapted version to patients. Results: The adaptation process produced a consensus version that preserved the semantic and cultural characteristics of the original scale. The statistical measures (KI = 1.00; I-CVI = 1.00; S-CVI/Ave = 1.00; S-CVI/UA = 1.00; CVR = 1.00) indicated satisfactory levels of agreement. The pilot test demonstrated the scale’s appropriateness and effectiveness for assessing dysarthria within the Chilean context, although some experts recommended reducing task repetition for patients prone to fatigue. Conclusions: The Chilean version of the BoDyS (BoDyS-CL) is a valid and useful tool for evaluating dysarthria in Chile. This study provides a foundation for further research and the systematic implementation of this scale in local clinical practice.